Functional annotation of native enhancers with a Cas9–histone demethylase fusion - Kearns, Nicola A; Pham, Hannah; Tabak, Barbara; Genga, Ryan M; Silverstein, Noah J; Garber, Manuel; Maehr, René (Nature methods, 2015)
Targeting a histone demethylase to specific enhancers with Cas9 allows modification of epigenetic marks at the enhancers. Understanding of mammalian enhancers is limited by the lack of a technology to rapidly and thoroughly test the cell type–specific function. Here, we use a nuclease-deficient Cas9 (dCas9)–histone demethylase fusion to functionally characterize previously described and new enhancer elements for their roles in the embryonic stem cell state. Further, we distinguish the mechanism of action of dCas9-LSD1 at enhancers from previous dCas9-effectors.